Prevalence of virological failure amongst WHO- defined immunological failure HIV patients on first line of highly active antiretroviral therapy in a tertiary care hospital in Haryana, India - Rajian, Manisha; Gill, Paramjeet S.; Chaudhary, Uma (International Journal of Research in Medical Sciences, 2016)
Background: In resource limited settings in India, monitoring of treatment in HIV patients taking highly active antiretroviral therapy is done by six monthly CD4 count instead of highly sensitive plasma viral load. Patients are subjected to viral load only when their CD4 count is low for the last 12 months. This protocol has a huge disadvantage as treatment failure is detected much later than it has actually occurred and switch over to second line therapy gets delayed by approximately one year. Methods: Plasma viral load (pVL) of 50 WHO defined immunological failure cases was done using RT-PCR to detect virological failure (VF). Results: Out of 50 WHO defined immunological failure cases, 16 percent had developed virological failure. Conclusions: Nearly one-sixth of WHO defined immunological failure (IF) cases had developed virological failure. These patients required second line highly active antiretroviral therapy (HAART) therapy but due to following of current treatment monitoring protocol, treatment got delayed by one year. Thus, amendment in national policy for monitoring ART is required to diagnose treatment failure early so that there is no delay in switching to second line ART and morbidity and mortality in these patients can be reduced.